The complex dynamics of flowing foam - Sexton, Michael B. (Trinity College (Dublin, Ireland). School of Physics, 2014)
We investigate the link between the non-linear macroscopic rheology of wet foams and the microscopic interactions at the bubble-scale, within the general framework of foams as a complex system. This rheology has been found to be well described in simulation by the soft disk model, which represents the bubbles in a two-dimensional foam as a series of overlapping disks, interacting via an elastic repulsion and a viscous dissipation. We simulate linearly sheared systems over a large range of strain rates, showing, for the first time in sinuilation, the transition between two regimes well-known from experiment; a low-strain regime with swirling, strongly non-affine motion, and a high strain rate regime comprising of laminar flow.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin